Study on The Effective Parameter of Gas Turbine Model with Intercooled Compression Process - Thamir K., Ibrahim; M. M., Rahman; Abdalla, Ahmed N. (Academic Journals, 2010)
In this paper parametric study of a gas turbine cycle model power plant with intercooler compression process was proposed. The power output and the efficiency are simulating with respect to the cycle temperatures and pressure ratio for a typical set of operating conditions. Simple gas turbine cycle calculations with realistic parameters are made and confirm that increasing the turbine inlet temperature no longer means an increase in cycle efficiency, but increases the work done. The analytical study is done to investigate the performance improvement by intercooling. The analytical formula for specific work and efficiency are derived and analyzed. The simulation results shows that increasing turbine inlet temperature and pressure ratio can still improve the performance of the intercooled gas turbine cycle.